The Effectiveness of the Life Skill Promoting Program and Family Participation on Life Skills Development and Intention to Quit Using Illicit Drug Among Juvenile Under Supervision by the Venue of Youth Observation and Protection - มีนา, นฤมล; ศุทธากรณ์, วีระพร (Nursing Journal CMU, 2018)
Juvenile detainees who are on illicit drug abuse and who are under the supervision of the Venue of Youth Observation and Protection should obtain proper life skills training before they are released. This can help in preventing them from returning to illicit drug abuse. This quasi experimental study is to explore the effectiveness of the life skill promoting program and family participation on the life skills development and intention to quit using illicit drugs among juvenile detainees who are under the supervision of the Venue of Youth Observation and Protection. Study participants included 42 juvenile detainees along with their 42 guardians for a total of 84. They were divided into 4 groups, each group composed of 20-24 participants (one juvenile detainee paired with one guardian). Each group participated in the program twice, one week at a time, and each time, lasted 2 hours. The program offered 8 activities including: relationship building activity, activity on the danger of illicit drug use, activity on the pathway to quit drugs, activity on sharing with other drug abusers, self-discovery activity, family and return to drug addiction activity, family strengthening activity, and goal setting activity. The data were collected before and after the implementation of the program in order to make a comparison. The instrument was self- administered questionnaire composed of 2 parts: life skill development and the intention to quit drugs. The data were analyzed using descriptive statistic and dependent t-test. The results showed that after the program implementation, the average scores of life skills development in all aspects and the intention to quit drugs were statistically significantly greater than those before the program implementation (p <0.01). The important factor that supported these outcomes was the group activity along with family member participation. Participants were given the chance to share and discuss, especially on area of support from the family members enhanced family members’ relationship and understanding. The intention of which is to develop self-sufficient life skills to prevent drug use. And intend to not go back to drug repetition.